Examining the impact of environmental, social, and governance integration on sustainable competitive advantage in digital platform: A case study of Tokopedia - Ajeng Damar Rarasati; Muhammad Dicka Ma'arief Alyatalatthaf (Journal of Economic, Business & Accounting Research, 2026)
Background: Environment, Social, and Governance (ESG) represents a comprehensive framework for assessing a company’s impact on environmental sustainability, social responsibility, and corporate governance practices. ESG is strategically employed to achieve sustainable competitive advantage, thereby fostering continuous innovation. This study examines Tokopedia, an e-commerce platform recognized for having one of the highest transaction growth rates in Indonesia. Methods: A qualitative descriptive approach is adopted, grounded in the ESG framework and the theory of Sustainable Competitive Advantage (SCA). Findings: This study revealed that, following its acquisition by PT GoTo operated in alignment with the ESG framework, sustained its competitive advantage, and consistently enhanced its digital platform. However, Tokopedia has not yet fully implemented ESG principles across environmental, social, and governance dimensions, thereby raising concerns regarding the long-term sustainability of its competitive advantage. Conclusion: Tokopedia is able to sustain its market position and remain competitive amidst intense industry rivalry and the volatility of global market conditions. Following its acquisition by TikTok, Tokopedia revised its business model by differentiating between Tokopedia and Shop Tokopedia, while simultaneously implementing efficiency measures through management restructuring. Novelty/Originality of this article: Integration of the ESG framework with the theory of SCA to analyze Tokopedia’s corporate evolution before and after major acquisitions by Gojek and ByteDance.